Pancasila and Religion - Icha Dwi Listari (Universitas of Muhammadiyah Makassar, 2023)
The background of this article is the values of Pancasila and religion. The religion that is adhered to by each individual, has the basics that have been reflected in Pancasila. However, as times change, Pancasila is always compared to a religion in which religion is the main guideline. Religion is paramount in everyday life, even though Pancasila values can be said to be in accordance with religious teachings. As for the author's goals in making articles, namely: 1) To understand Pancasila and Religion 2) To understand the relationship between Pancasila and Religion. In accordance with the author's background and goals, the method used is qualitative by collecting data in the form of literacy from books and articles that have been published. The result of this article is that the Indonesian people have accepted Pancasila as the foundation of national life and that all Indonesian citizens believe in God according to their respective religions and beliefs. Pancasila also accommodates differences and rejects the spirit of anti-tolerance when it includes dimensions of humanity, unity, democracy and social justice. So that Pancasila and Religion cannot be compared, because the values in Pancasila are in line with the teachings of all religions. Pancasila has a close relationship with Religion, this relationship presents a legal consequence in Indonesia which is based on Belief in One Almighty God.